Linking Career-Related Social Support to Job Search Behavior Among College Students: A Moderated Mediation Model - Zhangbo Xiong; Meihong Zeng; Yi Xu; Bin Gao; Quanwei Shen (Behavioral Sciences)
Background: Career-related social support (CRSS) significantly influences job search behavior (JSB). However, the mechanisms and boundary conditions through which CRSS impacts JSB, particularly during the COVID-19 pandemic, remain unclear. This study examines the mechanisms and boundary conditions through which CRSS influences the JSB among final-year college students during the COVID-19 pandemic, guided by social cognitive career theory (SCCT). Methods: A cross-sectional online survey was conducted in 2021 among 596 final-year college students from two public universities in China, during the COVID-19 pandemic. The survey collected data on CRSS, CDMS, employment pressure, and JSB. Results: The findings revealed that career decision-making self-efficacy (CDMS) partially mediates the relationship between CRSS and JSB. Moreover, employment pressure moderates both the direct and mediated pathways; when employment pressure is low, CRSS does not significantly enhance JSB, whereas under a high employment pressure, JSB significantly increases, with higher CRSS. In the mediated pathway, higher CDMS strongly predicts JSB under low employment pressure, but its influence diminishes as the employment pressure rises. Conclusions: These findings underscore the critical roles of CDMS and employment pressure in shaping JSB, offering valuable insights for career support initiatives to facilitate the transition of graduates into the workforce during challenging periods.